Pengaruh Model Pembelajaran Learning Cycle Terhadap Kemampuan Menulis Teks Persuasi Pada Siswa - Henny Dheana Putri; Azhar Umar (Pusat riset dan Inovasi Nasional, 2023)
This study aims to determine the cooperative learning model of the Learning Cycle type on the ability to write persuasive texts in class VIII students of SMP Negeri 8 Medan in the 2022/2023 Academic Year. The population in this study were all Grade VIII students of SMP Negeri 8 Medan for the 2022/2023 academic year with a total of 304 students. Of the 304 students, the sample size was 30 students. The research method used in this research is the one-group pre-test post-test design experimental method. The instrument used in this study is a description test. Hypothesis testing was carried out using the data